Increasing Diagnostic Uncertainties in Children With In Utero HIV Infection. Issue 8 (August 2019) - Millar, Jane R.; Mvo, Zodumo; Bengu, Nomonde; Fillis, Rowena; Sprenger, Ken; Matthews, Philippa C.; Archary, Moherndran; Ndung'u, Thumbi; Adland, Emily; Puertas, Maria C.; Martinez-Picado, Javier; Goulder, Philip
Abstract : We present a case of an in utero HIV-infected child, who on day 1 of life had a positive whole blood total nucleic acid test but viral load <20 RNA copies/mL. Dried blood spot total nucleic acid testing was negative on day 1, 10 and at 3 months, while on ART prophylaxis then positive at 5 months after prophylaxis ended. Retrospective peripheral blood mononuclear cells HIV DNA testing from day 1 of life was positive, confirming in utero infection. Abstract : Supplemental Digital Content is available in the text.